Rough country [compact disc, unabridged] - Sandford, John, 1944 February 23- (Sandford, John, 1944 February 23- Virgil Flowers novels., 2009)
In the third installment of John Sandford's Virgil Flowers series, a long-needed fishing trip gets interrupted when Flowers receives a call to investigate a murder at a nearby women-only resort in northern Minnesota. As he inquires about the woman's death, Flowers uncovers a shocking web of jealousy and deceit.